2017
DOI: 10.3389/fpubh.2017.00210
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Hazard Analysis in a Heterogeneous Workforce: Determinants of Work Stress in Blue- and White-Collar Workers of the European Steel Industry

Abstract: The European steel industry’s workforce is highly heterogeneous and consists of various occupational groups, presumably facing different psychosocial stressors. The few existing studies on the subject mainly focused on physical constraints of blue-collar workers, whereas the supposable psychosocial workload received only little research attention. This is remarkable considering the challenges associated with statutory required risk assessment of psychosocial hazards. Valid measures of hazard analysis must acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 64 publications
1
4
1
Order By: Relevance
“…The worse social relations or social interactions among the operational employees are due to the nature of their job that makes them work outside with little opportunity to interact with colleagues. The same results were obtained from the study conducted in European steel industry [31] . However, the operational personnel were in a better state in "possibilities for development" scale, which may be due to greater diversity of work, initiative, and greater use of expertise and opportunity to learn new things, comparing to office workers.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The worse social relations or social interactions among the operational employees are due to the nature of their job that makes them work outside with little opportunity to interact with colleagues. The same results were obtained from the study conducted in European steel industry [31] . However, the operational personnel were in a better state in "possibilities for development" scale, which may be due to greater diversity of work, initiative, and greater use of expertise and opportunity to learn new things, comparing to office workers.…”
Section: Discussionsupporting
confidence: 80%
“…Their study revealed that average scores of some scales such as predictability, role conflict, social relation and influence at work exceed the reference values in blue collar workers, in contrast average scores of possibility for development, meaning at work and role clarity showed slight deviation from reference values. In their study office workers had higher score in quantitative and emotional demand scales, compared to operational group and this finding is not in consistent with results of current study [31] .…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…A wide range of OHS hazards were identified, including biological hazards 14 chemical hazards, 65 ergonomic hazards, psychosocial hazards, and physical hazards. 59,62 The review has shown that healthcare professionals are at a significantly high risk of occupational related hazards. 56 Injuries and sickness prevent healthcare workers from discharging their duties effectively, which can have negative impact on the overall healthcare system in Taiwan.…”
Section: Discussionmentioning
confidence: 99%
“…Proper working communication devices and video surveillance, as well as panic buttons and alarm systems. 62 Administrative control: management policies make unequivocal declarations of non-violence/anti-abuse. 63 Management can encourage workers to participate in the design of forwardrotating (day-evening-night) shifts and work schedules that impose gradual shift changes and ease the adaptation to nonregular work shifts to ensure that all concerned get adequate sleep.…”
Section: Discussionmentioning
confidence: 99%